Hierarchical QoS-aware dynamic bandwidth allocation algorithm for wireless optical broadband access network - Ling Jiang; Ming-lei Fu; Zi-chun Le (2011 International Conference on Electronics, Communications and Control, 2011)
With the emergence of bandwidth-intensive applications, a novel wireless optical broadband access network (WOBAN) had been presented to improve both the access flexibility and bandwidth efficiency of network. WOBAN was set up as a convergence of an EPON and multiple WiMAX networks. Considering unique features of WOBAN, designing an applicable dynamic bandwidth allocation algorithm was significant to improve network performance and guarantee QoS requirement. Firstly, a concept of ONU-BS facility (OBF) was presented, in which a queue mapping scheme was carried out to adapt different queue mechanisms between EPON and WiMAX. Then, a hierarchical QoS-aware dynamic bandwidth allocation (HQA-DBA) algorithm was addressed, which supported bandwidth fairness at the OBF level and distinguished user QoS requirements for different traffics. The simulation results showed that HQA-DBA operates effectively in terms of average network delay and packet drop probability.